The equation x^2 + 2 = 6x has to be solved by completion of squares.

x^2 + 2 = 6x

=> x^2 - 6x + 2 = 0

=> x^2 - 6x + 9 + 2 = 9

=> (x - 3)^2 = 7

=> x - 3 = `sqrt 7` and x - 3 = `-sqrt 7`

=> x = `3 + sqrt 7` and x = `3 - sqrt 7`

**The roots of the equation are x = `3 + sqrt 7` and x = **`3 - sqrt 7`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now